2017
DOI: 10.5056/jnm16190
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Non-physiological, Surgically Tailored Ileocolic Anastomosis Using the Wireless Motility Capsule. A Pre- and Post-operative, Prospective, Within Subject Trial

Abstract: Background/AimsWireless motility capsule (WMC) detects the ileocolic junction (ICJ) in most non-operated patients. We find no data concerning this examination in patients where the ileocolic valve is replaced by a per definition incompetent, surgically created ICJ. We wanted to see if WMC could detect the ICJ after a right colectomy and assess the competency. MethodsProspective cohort study using a within-subject design to eliminate subject-subject variability. Selected patients operated with right colectomy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…One could also argue that the removal of the ileocolic valve could shorten the transit time. In a scintigraphic study performed by Fich et al, 20 no significant change in the SBTT was found after conventional right colectomy, suggesting In a previous study, 16 we not only confirmed the ability of the WMC to identify the ICJ after right colectomy but also showed that the main characteristics of the ICJ concerning pH-drop and pressure before the ICJ remained widely unchanged after surgical removal of the valve. These findings also seem to diminish the importance of the ileocolic valve.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…One could also argue that the removal of the ileocolic valve could shorten the transit time. In a scintigraphic study performed by Fich et al, 20 no significant change in the SBTT was found after conventional right colectomy, suggesting In a previous study, 16 we not only confirmed the ability of the WMC to identify the ICJ after right colectomy but also showed that the main characteristics of the ICJ concerning pH-drop and pressure before the ICJ remained widely unchanged after surgical removal of the valve. These findings also seem to diminish the importance of the ileocolic valve.…”
Section: Discussionsupporting
confidence: 77%
“…If not equivalent, the software gives the physician the opportunity to accept the computed values or to keep the values identified by the physician. (Note: the automatic identification is still too simplified and often fails to identify the landmarks [especially ICJ], whereas the physician-confirmed landmarks, based on the validated stereotypical pH profile, are more reliable 16 ). Furthermore, the software analyzes the mean and maximum pressures, the contractions per minute (CPM), and the motility index (MI) calculated as Ln (sum of amplitude  number of contractions þ1) through the different segments.…”
Section: The Analysismentioning
confidence: 99%
“…By contrast, ileocolonic anastomoses were as accurately recognized by CCE-2 as by optical colonoscopy. Thorsen et al recently showed the superiority of the motility wireless capsule endoscopy in the detection of both ileocolonic junction and ileocolonic anastomoses after right hemicolectomy [20]. However, this motility capsule is used to record intestinal contractions and locates the ileocolonic junction or anastomosis based on the motility pattern, in the absence of any video-recording and therefore cannot be compared with our results.…”
Section: Discussionmentioning
confidence: 75%